Total Laparoscopic Hysterectomy in Patients with Large Uteri: Comparison of Uterine Removal by Transvaginal and Uterine Morcellation Approaches. (22nd June 2016) - Wang, Haibo; Li, Ping; Li, Xiujuan; Gao, Licai; Lu, Caihong; Zhao, Jinrong; Zhou, Ai-ling
Abstract : The aim of this study was to compare the clinical results of total laparoscopic hysterectomy (TLH) for large uterus with uterus size of 12 gestational weeks (g.w.) or greater through transvaginal or uterine morcellation approaches. We retrospectively collected the clinical data of those undergoing total laparoscopic hysterectomies between January 2004 and June 2012. Intraoperative and postoperative outcomes were compared between patients whose large uterus was removed through transvaginal or morcellation approaches. The morcellation group has significantly shorter mean operation time and uterus removal time and smaller incidence of intraoperative complications than the transvaginal group (all P < 0.05 ). No statistical significant difference regarding the mean blood loss, uterine weight, and length of hospital stay was noted in the morcellation and transvaginal groups (all P > 0.05 ). In two groups, there was one patient in each group who underwent conversion to laparotomy due to huge uterus size. With regard to postoperative complications, there was no statistical significant difference regarding the frequencies of pelvic hematoma, vaginal stump infection, and lower limb venous thrombosis in two groups (all P > 0.05 ). TLH through uterine morcellation can reduce the operation time, uterus removal time, and the intraoperative complications and provide comparable postoperative outcomes compared to that through the transvaginal approaches.